Class and Identity on the Margins of Industrial Society: A Breton Illustration - Menzies, Charles R. (Anthropologica, 2022)
In this article the author draws upon his field work in Le Guilvinec, France during a period of crisis in the local fishery to explore the creation and reproduction of a local Bigouden identity. This identity emerged, replete with costume, rituals and festivals, out of an encounter between a metropolitan-driven industrial capitalism and a local, essentially non-capitalist, social formation. Here two aspects of how the "local" is integrated into and/or articulated with the "larger" are important: (1) the historical positioning of the Bigoudennie within Brittany, an internal hinterland of France supplying labour and raw resources; (2) the ways in which the emerging neoliberal processes of globalization structures, shapes and hinders the ability of local communities to wield any real control over local processes.